2005
DOI: 10.1038/sj.tpj.6500329
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-metabolizing gene polymorphisms and lipid levels in women with different hormonal status

Abstract: Endogenous and exogenous sex steroid hormones have multiple effects on lipid and lipoprotein metabolism. It is also known that estrogen has antiatherogenic actions, therefore we considered examining whether there was any association between polymorphisms in estrogen-metabolizing genes and lipid levels in women. We investigated the association between variants in genes related to estrogen biosynthesis (CYP19-TTTA n ) and estrogen catabolism (CYP1A1*2A, CYP1A1*2C, CYP1A2-Asn516Asn, CYP3A4*1B, and COMT-Val158Met)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…In a Mexican study, CYP1A1-m2 allele was significantly associated with high triglycerides (28), and in a Brazilian study in postmenopausal women the same allele was associated with high HDL-cholesterol (29). Unlike these studies, we have found no association between any of the CYP1A1 polymorphisms and lipid parameters and neither has a Japanese study in women with osteopenia or osteoporosis (30).…”
Section: Discussioncontrasting
confidence: 47%
“…In a Mexican study, CYP1A1-m2 allele was significantly associated with high triglycerides (28), and in a Brazilian study in postmenopausal women the same allele was associated with high HDL-cholesterol (29). Unlike these studies, we have found no association between any of the CYP1A1 polymorphisms and lipid parameters and neither has a Japanese study in women with osteopenia or osteoporosis (30).…”
Section: Discussioncontrasting
confidence: 47%
“…The same group performed a cross-sectional study investigating possible associations between polymorphisms in genes related to estrogen biosynthesis and estrogen catabolism. In both studies, SNP CYP3A4-V was the only CYP3A4 variant searched for in the upstream region (44). Since these investigations used PCR and restriction mapping analysis as a molecular biology approach, these punctual studies assumed CYP3A4-V to be the only possible variation without a previous SNP screening.…”
Section: Discussionmentioning
confidence: 99%
“…In that work, we also observed a positive correlation of LDL cholesterol change in response to atorvastatin with CYP3A4 and CYP3A5 mRNA levels. Regarding cholesterol-lowering interventions, the effect of the CYP3A4*1B variant was also tested in Brazilian postmenopausal women under HRT, and the authors reported lower LDL cholesterol levels in carriers of the CYP3A4*1B allele [50]. This result suggests that individuals carrying *1B allele could respond more effectively to pharmacological intervention compared to individuals carrying the CYP3A4*1A/1A genotype who may have low response to treatment, and also could present some toxic effects.…”
Section: Cyp3a4mentioning
confidence: 92%
“…However, some studies investigated the influence of polymorphisms after interventions with tamoxifen, hormone replacement therapy (HRT) and clozapine, an antipsychotic drug (Table 2). Almeida and co-workers [50] reported no association between the variants CYP1A1*2A, CYP1A1*2C and CYP1A2 p.Asn516Asn and the response to HRT monitored by changes in serum lipids. Similarly, a study evaluating the survival in women with breast cancer under tamoxifen treatment also showed no differences according to CYP1A1*2A and CYP1A1*2C genotypes [49].…”
Section: Phase I Drug Metabolizing Enzymes Cyp1a1 and Cyp1a2mentioning
confidence: 97%